What drives “fibrinolysis”? - Medcalf, R. L. (Hämostaseologie, 2015)
The timely removal of blood clots and fibrin deposits is essential in the regulation of haemostasis. This is achieved by the fibrinolytic system, an enzymatic process that regulates the activation of plasminogen into its proteolytic form, plasmin. This is a self-regulated event as the very presence of fibrin initiates plasminogen activation on the fibrin surface due to the presentation of exposed C-terminal lysine residues in fibrin that allow plasminogen to position itself via its lysine binding sites and to be more efficiently cleaved by tissue-type plasminogen activator (t-PA). Hence fibrin, the ultimate substrate of plasmin during fibrinolysis, is indeed an essential cofactor in the cascade. What has now come to light is that the fibrinolytic system is not solely designed to eliminate fibrin. Indeed, it is a broad acting system that processes a variety of proteins, including many in the brain where there is no fibrin. So what drives t-PA-mediated plasminogen activation when fibrin is not available?This review will describe the broadening role of the fibrinolytic system highlighting the importance of fibrin and other key proteins as facilitators during t-PA-mediated plasminogen activation.
Keywords: Fibrinogen; fibrin; fibrinolysis inhibitors; nervous system; plasminogen activators; plasminogen